Избранные произведения: стихотворения / А. В. Кольцов - Кольцов Алексей Васильевич (Удмуртия, 2010)
Экземпляры: аб. ДБ (20191205) / Инвентарный номер: 8466 / Цена: / Сис.шифр: Р1 / Авт.знак: К 62 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)1